The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.14738/abr.51.2565
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Evaluation of Metacognitive Awareness among Business Administration Students

Abstract: Purpose-The metacognitive approach is the new learning paradigm to enrich the standard of education in general and that of business education in particular The purpose of the study was to ascertain the views and opinions of Business Administration students regarding the metacognitive awareness. Design-A self-administered questionnaire was distributed to female undergraduate students. Statements cover between two major components, including knowledge about cognition and regulation of cognition. For analyzing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In addition, Young and Fry (2008) also found that there was a correlation between course grades and knowledge of cognition, as well as between grade point average and knowledge of cognition. The findings of Al Awdah et al (2017) also stated that the students' substantial awareness of metacognition is correlated positively and significantly with their academic performance.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, Young and Fry (2008) also found that there was a correlation between course grades and knowledge of cognition, as well as between grade point average and knowledge of cognition. The findings of Al Awdah et al (2017) also stated that the students' substantial awareness of metacognition is correlated positively and significantly with their academic performance.…”
Section: Resultsmentioning
confidence: 88%
“…The findings of this study were somewhat different from the results of previous studies. For instance , Sabna and Hameed (2016) found that most students have an average level of metacognitive awareness; (Panda, 2017) observed that the developments of metacognitive knowledge for both males and females were low; and Al Awdah et al (2017) showed that students had only a substantial awareness of metacognition.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, it impacts student learning outcomes that need to be revised (Wardoyo et al, 2021). In addition, students' lack of metacognitive awareness is often associated with students' need for more attention to the problem-solving and critical thinking processes (Awdah et al, 2017). Japanese learning informs that science teachers successfully encourage students in critical thinking (Kinoshita, 2022).…”
Section: Introductionmentioning
confidence: 99%